Sensitivity of a High-Speed Rail Development on Supply Chain and Logistics via Air-Rail-Road Freight Transportation - Liu, Rucheng; Stefanovich, Anton; Kaewunruen, Sakdirat (Frontiers in Built Environment, 2021)
The casual effect and synergy of high-speed rail development on the modal transport changes in supply chain and logistics have not been considered well during the initial phase of any rail project design and development. This has impaired the systems integration and connectivity among the modes of transport in a region. In the UK, High Speed 2, a large-scale railway project with a planned completion date in 2033, affects many transport stakeholders. The project influences the existing transport systems, but the transport systems integration design has not been well depicted, resulting in a pressing concern on systems connectivity and social value. This is evident by many public protests along the planned route of the project. Therefore, it is important to evaluate different aspects for any possible changes in supply chains caused by the development of high-speed rail networks. This paper provides the sensitivity analysis of supply chains via air-rail-road freight transportation and logistics stemming from the High Speed 2 case by the rigorous assessments into the capacity, performance and environmental changes that may follow the project's implementation. The research proposes a new method for estimation of consequences from a new transport project construction. The research findings demonstrate slight beneficial changes in freight transportation and logistics with a high potential for development; and reveal the project's weaknesses and opportunities for better systems integration and business synergy.